Efficient MySQL performance : best practices and techniques - Nichter, Daniel (O'Reilly Media, Inc., 2021)
You'll find several books on basic or advanced MySQL performance, but nothing in between. That's because explaining MySQL performance without addressing its complexity is difficult. This practical book bridges the gap by teaching software engineers mid-level MySQL knowledge beyond the fundamentals, but well shy of deep-level internals required by database administrators (DBAs). Daniel Nichter shows you how to apply the best practices and techniques that directly affect MySQL performance. You'll learn how to improve performance by analyzing query execution, indexing for common SQL clauses and table joins, optimizing data access, and understanding the most important MySQL metrics. You'll also discover how replication, transactions, row locking, and the cloud influenceMySQL performance. Understand why query response time is the North Star of MySQL performance Learn query metrics in detail, including aggregation, reporting, and analysis See how to index effectively for common SQL clauses and table joins Explore the most important server metrics and what they reveal about performance Dive into transactions and row locking to gain deep, actionable insight Achieve remarkable MySQL performance at any scale.